Peningkatan Higher Order Thinking Skills dengan Pembelajaran Berbasis Masalah - Ervina; Jackson Pasini Mairing; Yumiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2022)
Higher Order Thinking Skills (HOTS) or higher order thinking skills are demands of today's curriculum. However, the facts at SMPN 2 Kapuas Tengah Satu Roof show that students at the school do not yet have this ability. This study is intended to describe the effect of problem-based learning on HOTS. His research uses a quantitative approach with a quasi-experimental type. The population is junior high school students in Kapuas Tengah District, Kapuas Regency. The samples were class VII A and VIII A (experimental class), and class VII B and VIII B (control class). The instruments are pre-test and post-test. Data were analyzed using N-gain and covariate analysis. The conclusion shows that the increase in HOTS from pre-test to post-test as measured using N-gain in students who learn with problem-based lea[1]rning is better than those who learn using conventional learning. Problem-based learning has an effect on HOTS which is indicated by the HOTS of students in problem-based learning classes more than students in conventional learning classes.